A Prospective Cohort Study of Dysphagia After Subaxial Cervical Spine Surgery. Issue 8 (15th April 2021) - Sakai, Kenichiro; Yoshii, Toshitaka; Arai, Yoshiyasu; Hirai, Takashi; Torigoe, Ichiro; Inose, Hiroyuki; Tomori, Masaki; Sakaki, Kyohei; Yuasa, Masato; Yamada, Tsuyoshi; Matsukura, Yu; Oyaizu, Takuya; et al.
Abstract : Study Design: Prospective observational cohort study. Objective: To prospectively examine dysphagia after subaxial cervical spine surgery. Summary of Background Data: Although dysphagia after anterior cervical spine surgery is common and well-studied, it has rarely been examined in posterior subaxial cervical spine surgery. Methods: This study analyzed 191 consecutive patients (132 male, 59 female; mean age, 64.9 yrs) who underwent subaxial cervical spine surgery for degenerative disease and completed 1 year of follow-up. Anterior decompression with fusion (ADF) was performed in 87 patients, posterior decompression with fusion (PDF) in 21, and laminoplasty (LAMP) in 83. Dysphagia was evaluated by a self-administered questionnaire using the Bazaz dysphagia scale before, 6 months, and 1 year after surgery. Diagnosis, levels and number of operative segments, C2–7 lordotic angle (CL), O–C2 angle (OC2A), C2–7 range of motion (ROM), Japanese Orthopedic Association for cervical myelopathy (C-JOA) score, and neck pain visual analog scale (VAS) were examined. Results: Thirty-two patients (16.8%) reported dysphagia before surgery. New dysphagia after surgery, defined as more than or equal to 1 grade worsening of the Bazaz score after surgery compared with the preoperative status, was observed in 38 patients (19.9%) at 6 months and 32 patients (16.8%) at 1 year. The incidence of new dysphagia at 1 year was 25.3% in the ADF group, 23.8% in the PDF group, and 6.0% in the LAMP group. Fusion surgery (ACDF or PDF) and increased CL after surgery were found as risk factors at 1 year in multivariate analysis; receiver operating characteristic analysis determined a postsurgical change in CL cutoff of 5°. Conclusion: Fusion surgery and increased CL after surgery were risk factors for development of dysphagia after subaxial cervical spine surgery. Cervical alignment change due to anterior and posterior fusion surgery can cause postoperative dysphagia. Level of Evidence: 3 Abstract : We conducted a prospective observational cohort study of dysphagia after subaxial cervical spine surgery. The incidence of new dysphagia at 1 year after surgery was 25.3% after anterior decompression with fusion, 23.8% after posterior decompression with fusion, and 6.0% after laminoplasty. Fusion surgery and more than 5° increase in C2–7 angle after surgery were risk factors.